Evidence on antimicrobial activity of essential oils and herbal extracts against Yersinia enterocolitica - A review. (June 2022) - Durofil, Andrea; Maddela, Naga Raju; Naranjo, Reinier Abreu; Radice, Matteo
Abstract: Yersinia enterocolitica is a very common food-borne pathogen which causes gastrointestinal infections (yersiniosis) in humans and a wide array of animals (e.g. cattle, deer, pigs, and birds). Due to the increasing interest in innovative plant-based substances as common food preservatives, several essential oils and herbal extracts have been investigated deeply that resulted in the emergence of novel anti-Yersinia additives. We reviewed relevant work done by 53 researchers covering literature from the year 2002 to till date. Some species such as Origanum vulgare, Rosmarinus officinalis, Thymus vulgaris, Ocimum basilicum have been extensively investigated and identified that 1, 8-cineole, linalool and γ-terpinene as compounds found in the essential oils of these plants have anti-Yersinia activity active food packaging agents. In the same direction, some promising results have been mentioned about the herbal extracts of Murrya koenigii, Tanacetum vulgare and Tanacetum balsamita, but further investigations are needed for their sustainable implications. According to hierarchical cluster analysis, we found that Lamiaceae and Lauracea as the most significant families with anti-Yersinia activity. Towards the end, we proposed new research trends in order to enhance a global knowledge about the use of natural products against Y. enterocolitica . Highlights: Y . enterocolitica is a pathogen which causes gastrointestinal infections. Essential oils and herbal extracts are a source of plant-based food preservatives. Lamiaceae and Lauracea families have been considered from researchers. O. vulgare, R.s officinalis, T. vulgaris, O. basilicum shoved promising results.